The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/0003319715618039
|View full text |Cite
|
Sign up to set email alerts
|

Association of β-Adrenergic Receptor Gene Polymorphisms With Acute Coronary Syndrome and Cardiovascular Risk Factors in an Arab Population

Abstract: We evaluated the association between beta-adrenergic receptor genes (ADRB1 and ADRB2) polymorphism, cardiovascular risk, and acute coronary syndrome (ACS) in individuals from an Arab ethnicity. A total of 388 Qatari participants were assessed and genotyped for ADRB1 (rs1801252 & rs1801253) and ADRB2 (rs1042718 & rs1042713) polymorphisms using allele-specific PCR. Minor allele frequencies (MAF) in each single-nucleotide polymorphisms (SNPs) did not show statistically significant difference between cases and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The 5 nuclease assay was performed using 20 ng of genomic DNA, 1× TaqMan Universal PCR Master Mix (Applied Biosystems) and 1× primer/probe mix using the correct conditions for an extension by the manufacturer's instructions. Negative controls were used as previously described [22].…”
Section: Genotyping Of the Polymorphisms Of The Variants Rs4986790 Anmentioning
confidence: 99%
“…The 5 nuclease assay was performed using 20 ng of genomic DNA, 1× TaqMan Universal PCR Master Mix (Applied Biosystems) and 1× primer/probe mix using the correct conditions for an extension by the manufacturer's instructions. Negative controls were used as previously described [22].…”
Section: Genotyping Of the Polymorphisms Of The Variants Rs4986790 Anmentioning
confidence: 99%
“…The ADRB2 gene encodes the β2-adrenoreceptor, which plays a vital role in regulating the cardiovascular system ( Dai et al, 2021 ). Several SNPs in the ADRB2 gene could impact cardiovascular activity, thereby altering the risk of hypertension ( El-Menyar et al, 2015 ; Huang et al, 2018 ). Nielsen and colleagues found that carriers of the minor allele (G) showed a tendency toward vasodilation and high cardiac output during anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the genetic basis of CHD in the ME. 18,19 Prior GWAS in ME populations failed to replicate several known CHD loci. [20][21][22] To address this gap in knowledge, we initiated the Qatar Cardiovascular Biorepository in 2014 to collect DNA and plasma of CHD cases and controls, with the goal of studying the "omics" of CHD in Qatari individuals.…”
mentioning
confidence: 99%